Heavy Chain Transfer by Tumor Necrosis Factor-stimulated Gene 6 to the Bikunin Proteoglycan - Lamkin, Elliott (J Biol Chem, 2015)
We present data that hyaluronan (HA) polysaccharides, about 14–86 monosaccharides in length, are capable of accepting only a single heavy chain (HC) from inter-α-inhibitor via transfer by tumor necrosis factor-stimulated gene 6 (TSG-6) and that this transfer is irreversible. We propose that either the sulfate groups (or the sulfation pattern) at the reducing end of the chondroitin sulfate (CS) chain of bikunin, or the core protein itself, enables the bikunin proteoglycan (PG) to accept more than a single HC and permits TSG-6 to transfer these HCs from its relatively small CS chain to HA. To test these hypotheses, we investigated HC transfer to the intact CS chain of the bikunin PG, and to the free chain of bikunin. We observed that both the free CS chain and the intact bikunin PG were only able to accept a single HC from inter-α-inhibitor via transfer by TSG-6 and that HCs could be swapped from the bikunin PG and its free CS chain to HA. Furthermore, a significant portion of the bikunin PG was unable to accept a single heavy chain. We discuss explanations for these observations, including the intracellular assembly of inter-α-inhibitor. In summary, these data demonstrate that the sulfation of the CS chain of bikunin and/or its core protein promote HC transfer by TSG-6 to its relatively short CS chain, although they are insufficient to enable the CS chain of bikunin to accept more than one HC in the absence of other cofactors.